Small cell oesophageal carcinoma: an institutional experience and review of the literature. - Hudson, E; Powell, J; Mukherjee, S; Crosby, T; Brewster, A; Maughan, T; Bailey, H; Lester, J (2007)
Primary small cell oesophageal carcinoma (SCOC) is rare, prognosis is poor and there is no established optimum treatment strategy. It shares many clinicopathologic features with small cell carcinoma of the lung; therefore, a similar staging and treatment strategy was adopted. Sixteen cases referred to Velindre hospital between 1998 and 2005 were identified. Patients received platinum-based combination chemotherapy if appropriate. Those with limited disease (LD) received radical radiotherapy (RT) to all sites of disease on completion of chemotherapy. Median survival of all patients was 13.2 months. Median survival of patients with LD was significantly longer than those with extensive disease (24.4 vs 9.1 months, P=0.034). This is one of the largest single institution series in the world literature. Combined modality therapy using platinum-based combination chemotherapy and radical RT may allow a nonsurgical approach to management, avoiding the morbidity of oesophagectomy. Prophylactic cranial irradiation is controversial, and should be discussed on an individual basis.